An Appraisal of Financial Sustainability of Dairy-Based Farmer Producer Companies in India (Indian Journal of Extension Education, 2021)
The purpose of the study is to assess the financial performance of selected dairy-based producer companies in India. The data were collected from four dairy-based FPCs which were more than three years old from three states of India i.e., Madhya Pradesh, Uttar Pradesh, and Rajasthan. Major four financial performance indicators i.e., liquidity, solvency, efficiency, and profitability were studied. Each indicator has four ratios and thus a total of 16 ratios were used for financial performance assessment. A financial ratio analysis methodology was used and performance was indicated by the performance score method. The study found that all four Farmer Producer Companies are in the red zone and perform poorly in terms of solvency, efficiency, and profitability during the three years under study. The overall Combined Performance Score of all four FPCs was in the yellow (average) zone. The study suggests that suitable measures like increase the share of stakeholders, fund generation and financial support from donor institutions, effective and efficient business plan for the company, suitable marketing linkage, and strategy, enhance the business capacity of the company, etc. should be taken immediately to improve the financial performances of FPCs in India to make them sustainable and viable.